Wage coordination and unemployment dynamics in Norway and Sweden - Bergljot Bjørnson Barkbu; Ragnar Nymoen; Knut Røed (University of Oslo, Department of Economics, 2001)
From a detailed study of the yearly wage bargaining rounds in Norway and Sweden, we construct time series of five complemetary coordination indices. Econometrics is used to evaluate the importance of the coordination indicators for our understanding of the changes in the rates of unemployment in the two countries. The results show that there is considerable similarity between the two countries, e.g., in terms of the estimated effects of macroeconomic variables on unemployment, The coefficients are recursively stable over the the 1980s and 1990s. Simulation shows that the models imply numerically important effects of wage coordination on the rates of unemployment in both countries. – unemployment ; wage setting ; economic institutions ; corporatism ; centralization ; decentralization ; income policies ; econometric modelling
Keywords: C32; J51; J52; P11; P17; P52; 330; Lohnbildung; Arbeitslosigkeit; Vergleich; Norwegen; Schweden